Review of Shakespeare’S Passionate Characters: a Study of Ophelia: The Tragic Inspiration Behind Shakespeare's Ophelia (Journal of Advances and Scholarly Researches in Allied Education, 2013)
It is assumed that the name Ophelia could be taken from afamous Italian pastoral novel called Arcadiawhere the name Ophelia belonged to a male character. However, theportrait of the tragic Ophelia as such was probably influenced by memories ofShakespeare’s childhood. When he was sixteen years old, a young unmarried girl,Catherine Hamlet, drowned herself in the river Avon not far away from the townof Stratford, and this unhappy event firmly engraved in boy's fantasy, whichafter years created the vision of a touching girl called Ophelia